Β‐Diketiminate Aluminum Dihydride is a Valuable Precursor for the Preparation of Acyclic and Cyclic Systems. Issue 4 (20th October 2022) - Huo, Shuai‐Cong; Li, Yao; Ji, Peng‐Fei; Zhang, De‐Xiang; Zhang, Zhi‐Jiao; Yang, Ying; Roesky, Herbert W.
Abstract: Treatments of β ‐diketiminate aluminum dihydride LAlH2 (L=HC[C(Me)N(Ar)]2, Ar=2, 6‐ i Pr2 C6 H3 ) with (2‐chlorophenyl)methanol, 2, 3‐dimethylbutane‐2, 3‐diol, 2, 2‐dimethylpropane‐1, 3‐diol, 2, 2‐bis(bromomethyl)propane‐1, 3‐diol, and p ‐diphenol resulted in the formation of compounds containing the C−O−Al−O−C linkages, including the acyclic LAl[( μ ‐O)CH2 ( o ‐Cl−C6 H4 )2 ]2 (1 ), the five‐membered ring LAl[( μ ‐O)CMe2 ]2 (2 ), the six‐membered ring LAl[( μ ‐O)CH2 ]2 CMe2 (3 ) and LAl[( μ ‐O)CH2 ]2 C(CH2 Br)2 (4 ), and the macrocyclic [LAl( μ ‐O)2 ( p ‐C6 H4 )]4 (5 ), respectively. These practices prove that β ‐diketiminate aluminum dihydride is a valuable precursor for the preparation of acyclic and cyclic systems. 1 –5 were characterized by melting point, 1 H and 13 C NMR, FT‐IR, and single‐crystal X‐ray diffraction studies. Abstract :